2015
DOI: 10.5152/tao.2015.694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Septorhinoplasty on Olfactory Function: Assessment Using the Brief Smell Identification Test

Abstract: Objective: Septorhinoplasty (SRP), one of the most commonly performed rhinologic surgery procedures, can affect olfactory function; however, the findings of studies investigating smell following SRP are controversial. We used a culturally adapted modified Brief Smell Identification Test (B-SIT) to investigate the long-and short-term effects of SRP on olfactory function. Methods:We enrolled 59 patients admitted to the EarNose-Throat Clinic, who were complaining of external nasal deformity and nasal obstruction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…On the other hand, increasing evidence suggests that SRP can also be a treatment for some cases of OD 35 . This notion is supported by studies that reveal that early preoperative (6w) scores did not improve or were worse than before the SP or SRP, only to improve later in the follow-up period 24,29,[36][37][38] . A rational analysis is lacking in the literature regarding the long-term effects of SRP on OF.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, increasing evidence suggests that SRP can also be a treatment for some cases of OD 35 . This notion is supported by studies that reveal that early preoperative (6w) scores did not improve or were worse than before the SP or SRP, only to improve later in the follow-up period 24,29,[36][37][38] . A rational analysis is lacking in the literature regarding the long-term effects of SRP on OF.…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, three of the analyzed studies demonstrated olfactory improvement with quite short follow-up intervals 13,29,30 , suggesting that there may be some heterogeneity between patients and/or measuring techniques between investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Dengiz, et al [27] in a study on effects of septorhinoplasty on olfactory function using brief smell identification test (BSIT) tool suggested BSIT as a fast and reliable tool for testing olfactory function [27]. BSIT includes 12 pens and smells to assess patients' olfactory function.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 There are studies in literature that have reported olfactory disorders forming in the early period after nasal surgery that have recovered in the long term with the elimination of edema and inflammation. 17,19 In a study by Apuhan et al, biopsies taken from lateral, anterior, and medial surfaces of concha of patients operated on for a diagnosis of CB were found to include nerve tissue at rates of 81.4%, 60%, and 32.8%, respectively, and it was also stated that lateral turbinectomy could cause loss of the sense of smell. 1 The BSIT is an easily completed test with proven objectivity, validity, and reliability, not affected by the educational level, ethnicity, or language of the respondents.…”
Section: Discussionmentioning
confidence: 99%